-2p+5p-9=3(p-4)-5

Simple and best practice solution for -2p+5p-9=3(p-4)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2p+5p-9=3(p-4)-5 equation:


Simplifying
-2p + 5p + -9 = 3(p + -4) + -5

Reorder the terms:
-9 + -2p + 5p = 3(p + -4) + -5

Combine like terms: -2p + 5p = 3p
-9 + 3p = 3(p + -4) + -5

Reorder the terms:
-9 + 3p = 3(-4 + p) + -5
-9 + 3p = (-4 * 3 + p * 3) + -5
-9 + 3p = (-12 + 3p) + -5

Reorder the terms:
-9 + 3p = -12 + -5 + 3p

Combine like terms: -12 + -5 = -17
-9 + 3p = -17 + 3p

Add '-3p' to each side of the equation.
-9 + 3p + -3p = -17 + 3p + -3p

Combine like terms: 3p + -3p = 0
-9 + 0 = -17 + 3p + -3p
-9 = -17 + 3p + -3p

Combine like terms: 3p + -3p = 0
-9 = -17 + 0
-9 = -17

Solving
-9 = -17

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (3z+1)(4z+1)(6z+1)(12z+1)=2 | | 7x-4=3x+1+9x-5 | | -4-7x=2x+15 | | 4r-9=55 | | 4x+14(-14)-3+(-14)= | | 16+8x=24+6x | | -4(-x+4)=-4x+16 | | 16-4x= | | 7x-4=-3x+1+9x-5 | | x(30-x)=176 | | -94=-17+-7m | | -4(x-4)=-4x+16 | | 7n=50+35 | | 5x-10=14+7x | | 0.2x+0.15(50)=25.5 | | 5=RAIZ(2)+6RAIZ(3)+RAIZ(2)-2RAIZ(3) | | (-9r^3+2r-1)-(-5r^2+6x^2)= | | y=x(x^2-3) | | 8w-21=11 | | -3(-4-6y)+7(-y-5y)=-8 | | 4(1x+9)=56 | | 10(12-5)= | | -m+68=10 | | -3(-4-6y)+7(-y-5w)=-8 | | 10+8q=11+7q | | 85=10-2.5(c) | | 28=5x-2x+4 | | (5x^2-3x+7x)+(4x^2+2x^2+7x)= | | 3y-4y=-4y+29 | | 6(x-1)+3=13 | | 22+4y=50 | | 5x^(2/3)-19x^(1/3)-4 |

Equations solver categories